Clostridium perfringens and C. difficile in parvovirus-positive dogs - Silva, Rodrigo Otávio Silveira; Dorella, Fernanda Alves; Figueiredo, Henrique Cesar Pereira; Costa, Érica Azevedo; Pelicia, Vanessa [UNESP]; Ribeiro, Bruna Letícia Devidé [UNESP]; Ribeiro, Marcio Garcia [UNESP]; Paes, Antonio Carlos [UNESP]; Megid, Jane [UNESP]; Lobato, Francisco Carlos Faria (Elsevier, 2017)
The aim of this study was to investigate Clostridium difficile and Clostridium perfringens in 82 diarrheic dogs positive for canine parvovirus type 2 (CPV). Enterotoxigenic C. perfringens type A was isolated from three (3.6%) dogs. One (1.2%) strain was also positive for NetE- and NetF-encoding genes, which are commonly associated with diarrhea in dogs. Toxigenic C. difficile was isolated from one animal (1.2%), which was also positive for A/B toxins. The present study identified C. difficile and C. perfringens infection in CPV-positive dogs. Further studies are necessary to clarify if clostridial infections may predispose or potentiate CPV-infection in dogs or vice versa.
Keywords: Canine; CPV-2b; Diarrhea; Hemorrhagic enteritis; Parvovirus